Dampak Kenaikan Upah Minimum Terhadap Kesenjangan Upah Antar Gender: Kasus di Seluruh Provinsi di Indonesia - Leonardo Alexius Simamora; Diah Widyawati (Jurnal Ekonomi Dan Statistik Indonesia, 2022)
Wage gap disparities have become polemic in almost all countries in the world, especially in developing countries. Minimum wage is present as a policy on wage system that aims to be a safety net for workers. Although this policy is not a gender-oriented policy, if the number of women and the actual wage distance of women's minimum wage is lower than that of men, then the minimum wage may raise the wage gap. This study aims to examine the impact of minimum wage increases on wage gap across all provinces in Indonesia by using counterfactual methods on wage distribution. The results of this study indicate that the impact of minimum wages in Indonesia actually widen the wage gap between the gender especially on workers in the distribution of low wages. The impact of regional minium wages varies across provinces.